(untitled) (Journal of Additive Manufacturing Technologies, 2022)
Titanium is one of the most desirable engine materials in the cold sections of aero engines due to its low density and high strength. Titanium suffers from oxygen entrapment by the reason of heat treatment, high-temperature exposure and produced an oxygen-rich layer referred to as an alpha case. Laser Powder Bed Fusion (L-PBF) supports to production of the desired geometries that have high complexity. As a material fusion process, L-PBF causes parts to encounter the alpha case due to high temperature melting even though the process is done in an inert atmosphere. Since L-PBF produced parts that have high surface roughness value due to the semi-melted powders on the surfaces, it is difficult to remove the alpha case layer totally. In this study, Ti6Al4V ELI parts were produced by L-PBF and measured alpha case layer thickness before and after heat treatment and chemical milling. The three sandblasting (SB) parameters were used to facilitate a chemical attack on the parts surface before chemical milling processes. This study demonstrated that the SB process enhanced the chemical milling performance of L-PBF produced samples and the alpha case layer was successfully removed.